Optimization of 2-α-Chloroethylphosphonic acid synthesis-important intermediate product in the production of phosphonates through hemolytic phosphorylation method of vinyl acetate by dimethyl phosphate - Bernadin, ELEGBEDE (My University, 2019)
The discovery in 1954 by Pudovik A.N., of the phosphorylation reaction [1] has made the method one of the most important, easiest and accessible ways for synthesis of very large spectra of phosphonates. The interest for this synthesis résides in the multiple medico-biological activities, the properties and the uses of the products resulting from the aforesaid synthesis. As a matter of fact, phosphonates are used in medicine for HIV therapy (tenofovir), osteoporosis treatment during women ménopause, in agriculture as plant growth regulator, herbicides and fongicides; they also served as lubricants and foel additives, anticorrosion additives, extractants and détergents. Phosphonates are equally used for eutrophication of aquatic environments to improve the fish breeding (fish farming) outcome. For ail thèse différent reasons, the challenge for 2-a-chloroethylphosphonic acid synthesis optimisation-an important intermediate product in phosphonates production was undertaken.In a four neck-reactor of 0.25L capacity equipped with an agitator, a thermometer, a reverse refrigerator, a funnel with tap and paddle for inert gas introduction, 80mL of freshly distilled dimethyl phosphite has been poured at a température between 155-160°C. With intensive agitation in nitrogen atmosphère, 0.4mL of di-tertio-butyl peroxide has been added. Atthe end of the dosage, the mixed product is agitated for thirty (30) more minutes at the same température gap (155-160°C); the non-reacted dimethyl phosphite excess is extracted through a water boiling bain-marie at a residual pressure of 20mm Hg. The remaining part is farther distilled under vacuum conditions, collecting the fraction of boiling température 108-110°C (at a pressure of 4mmHg). The 2-dimethoxy-phosphoryl acetic acid ethyl ester is once more purified with lg of sodium bicarbonate in order to extract the traces of dimethyl phosphite. The final resulting yield is: 36.0g-(86.7%) nj^l.4365.
Keywords: phosphorylation; reactor; inert gas; 2-dimethoxy-phosphoryl acetic acid ethyl ester; plant growth regulator; corrosion additives; fuel additives.